Nonperiodic locally solvableT(Ā)-groups - Kuzennyi, N. F. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We constructively describe nonperiodic locally solvableT(Ā) -groups and select three types of groups of this sort.